2019
DOI: 10.1038/s41380-019-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of sleep restriction therapy for insomnia

Abstract: Insomnia is the most common sleep disorder among adults, especially affecting individuals of advanced age or with neurodegenerative disease. Insomnia is also a common comorbidity across psychiatric disorders. Cognitive Behavioral Therapy for Insomnia (CBT-I) is the first-line treatment for insomnia; a key component of this intervention is restriction of sleep opportunity, which optimizes matching of sleep ability and opportunity, leading to enhanced sleep drive. Despite the well-documented efficacy of CBT-I, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…1C). To allow for comparison with human sleep measures, we assessed orthologous sleep metrics (22) and found SE to be decreased (Fig. 1D).…”
Section: Kismet Mutants Recapitulate Human Sleep Maintenance Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). To allow for comparison with human sleep measures, we assessed orthologous sleep metrics (22) and found SE to be decreased (Fig. 1D).…”
Section: Kismet Mutants Recapitulate Human Sleep Maintenance Defectsmentioning
confidence: 99%
“…By restricting the sleep opportunity window, SRT enhances sleep drive leading to a more efficient and consolidated sleep. We recently established a model for SRT in flies and demonstrated that SRT in flies improves SE and continuity in short-sleeping Drosophila mutants and a fly model for Alzheimer's disease (22). Whether SRT can reverse sleep defects in neurodevelopmental disorders models is unknown.…”
Section: Sleep Restriction Therapy Restores Sleep Architecture In Glial Kismet Modelsmentioning
confidence: 99%
“…Insomnia is defined as a purely subjective complaint of dissatisfaction with sleep quality and quantity in spite of adequate opportunity for sleep, which is the most common sleep disorder among adults, especially affecting individuals of advanced age or with neurodegenerative disease. [ 1 ] It is characterized by persistent difficulty initiating or maintaining sleep, along with associated daytime impairment. [ 2 ] As much as one-third of the population experiences transient insomnia symptoms at any given time.…”
Section: Introductionmentioning
confidence: 99%
“…Further, genetic or pharmacological induction of sleep alleviates disease progression in fly models of Alzheimer’s Disease, suggesting that sleep is neuroprotective [16,38,39]. Both sleep and Wallerian degeneration are disrupted in old flies, raising the possibility that restoration of sleep in old animals could protect against age-related decline in glial function [8,36,40]. The identification of sleep-dependent changes in the function and morphology of ensheathing glia will facilitate studies of the effects of sleep on glial function in aging and disease models.…”
Section: Resultsmentioning
confidence: 99%